Metal-organic framework adsorbents and membranes for separation applications - Duan, Jingui; Pan, Yichang; Liu, Gongping; Jin, Wanqin (Current opinion in chemical engineering, 2018)
With versatile chemical and engineering design, the more attention of metal-organic framework (MOF) material is shifting from its fundamental studies to industrial applications, such as engineering MOF adsorbents and membranes for selective guest capture and separations. Learned from zeolites, various effective strategies in material design, adsorbents assembly, and membranes fabrication have enabled the MOFs gradually to approach high industrial standards, bearing their unique chemical and physical properties. In this review, we focus on the important factors that may affect the practical applications of MOF adsorbents and MOF membranes.